If Politics Is the Problem, How Can External Actors Be Part of the Solution? - Devarajan, Shantayanan; Khemani, Stuti (World Bank, Washington, DC, 2016)
Despite a large body of research and evidence on the policies and institutions needed to generate growth and reduce poverty, many governments fail to adopt these policies or establish the institutions. Research advances since the 1990s have explained this syndrome, which this paper generically calls "government failure," in terms of the incentives facing politicians, and the underlying political institutions that lead to those incentives. Meanwhile, development assistance, which is intended to generate growth and reduce poverty, has hardly changed since the 1950s, when it was thought that the problem was one of market failure. Most assistance is still delivered to governments, in the form of finance and knowledge that are bundled together as a "project." Drawing on recent research on the politics of government failure, the paper shows how traditional development assistance can contribute to the persistence of government failures. It proposes a new model of development assistance that can help societies transition to better institutions. Specifically, the paper suggests that knowledge be provided to citizens to build their capacity to select and sanction leaders who have the political will and legitimacy to deliver the public goods needed for development. As for the financial transfer, which for various reasons has to be delivered to governments, the paper proposes that this be provided in a lump sum manner (that is, not linked to individual projects), conditional on the government following broadly favorable policies and making information available to citizens.